Using Fsvm Classfication Algorithm For Extracting Texts On Internet - Vu, Thanh Nguyên; Truong, Nhật Quang (Journal of Technical Education Science, 2008)
This paper is used automatically to extract information and classify texts by SVM method, FSVM method with fuzzy multiclass classification. This research result is used to collect information from admin webpage of local goverment departments, offices for providing citizens, companies about news of HCM city goverment policy, needed information for operating public admin.